The Gadamerian hermeneutics for a mesoeconomic analysis of Cultural Heritage. Issue 3 (5th August 2019) - Settembre Blundo, Davide; Maramotti Politi, Anna Lucia; Fernández del Hoyo, Alfonso Pedro; García Muiña, Fernando Enrique
Abstract : Purpose: The purpose of this paper is to explore the application of a hermeneutic-based approach as innovative way to study the Cultural Heritage management in a mesoeconomic space. Design/methodology/approach: The paper builds a theoretical framework based on the analysis of relevant literature in the field of cultural economics, heritage economics and conservation and restoration techniques. Then, after having defined the conceptual hypothesis, a hermeneutical interpretative model is designed for the analysis of the processes of Cultural Heritage management with particular regard to the strategies of stakeholder engagement. Findings: The research shows how the mesoeconomic space is that border area where it is possible to solve more easily the conflicts that arise as a result of the different expectations of stakeholders. Hermeneutical analysis, applied in iterative form, allows us to find common connections, points of contact and convergences between the interpretative horizons of the various stakeholders. Practical implications: The application of the interpretative model allows the identification of the expectations of stakeholders, improving the knowledge of the tangible and intangible attributes of works of art, in order to design appropriate interventions of restoration, conservation and valorization. Social implications: The new model of analysis, based on hermeneutic methodology, is designed to understand and describe the social and economic relations between the different stakeholders involved in the management of Cultural Heritage. Originality/value: This paper examines for the first time the Cultural Heritage sector within the mesoeconomic area between the micro and the macroeconomy. In addition to this mesoeconomic analysis and conceptual approach, the authors introduce as methodology the economic hermeneutics that represents an innovative tool in the field of economic and business disciplines.